Combined transarterial chemoembolization and radiofrequency ablation for small treatment-naïve hepatocellular carcinoma infeasible for ultrasound-guided radiofrequency ablation: long-term outcomes. (July 2018) - Hyun, Dongho; Cho, Sung Ki; Shin, Sung Wook; Park, Kwang Bo; Lee, Sang Yub; Park, Hong Suk; Do, Young Soo
Background: Ultrasound (US)-guided radiofrequency ablation (RFA) for small hepatocellular carcinoma (HCC) is often infeasible due to unfavorable location and poor conspicuity. Those small HCCs can be treated with combined transarterial chemoembolization (TACE) and RFA. Purpose: To evaluate long-term outcomes of combined TACE and RFA for small treatment-naïve HCC infeasible for US-guided RFA. Material and Methods: Between February 2009 and January 2014, 69 patients with small (≤3 cm) HCC infeasible for US-guided RFA received TACE and subsequent RFA in one session as a first-line treatment. Local tumor progression (LTP), overall survival (OS), and event-free survival rates were evaluated. Univariate and multivariate analyses were conducted to identify prognostic factors. Results: Cumulative rates of LTP were 4.4%, 6.8%, 8.2%, 9.5%, and 9.5% at one, two, three, five, and seven years, respectively. Cumulative one-, two-, three-, five-, and seven-year OS rates were 100%, 95%, 89%, 80%, and 80%, respectively. Cumulative one-, two-, three-, five-, and seven-year event-free survival rates were 81%, 63%, 54%, 31%, and 20%, respectively. No significant prognostic factors for LTP, OS, and event-free survival were identified in univariate analysis. Conclusion: Combined TACE and RFA appears to be an effective treatment for small treatment-naïve HCC infeasible for US-guided RFA in terms of LTP and OS.